Palaeoenvironmental interpretation of a sand-dominated coastal system of the Upper Miocene of eastern Guadalquivir Basin (south Spain): fossil assemblages, ichnology and taphonomy - Reolid, Matias; Garcia-Garcia, Fernando; Reolid, Jesus; de Castro, Arancha; Bueno, Jose; Martín-Suárez, Elvira (Journal of Iberian Geology, 2016)
The palaeontological study of fossil assemblages from the Upper Miocene (Tortonian) marine deposits of the eastern sector of the Guadalquivir Basin allows interpreting palaeoenvironmental and depositional conditions when this basin acted as a connection between the Atlantic Ocean and the Mediterranean Sea. The Arroyo Escobar section represents a sand-dominated coastal system in transition to offshore deposits located on the northern margin of the basin. The materials are constituted by alternations of highly bioturbated fine sands (Skolithos ichnofacies) and bioclast-rich cemented coarse sands. In this context, several fossil remains of vertebrates have been recorded, corresponding to marine mammals, mainly cetaceans and pinniped. The remains are incomplete due to different factors, mainly the action of large scavengers. The palaeoenvironmental interpretation of these deposits has been based on the analysis of lithofacies, as well as the study of trace fossils and benthic macroinvertebrate assemblages. Background dynamic was affected by the input of high energy deposits coming from shallower and more proximal environments which incorporates allochthonous faunas with different preservation. In addition, this work is the first study of fossil marine mammals in the eastern sector of the Guadalquivir Basin.